NEURAXIAL METHODS OF PAIN RELIEF IN LABOR - R. T. Shakirov; S. V. Kinzhalova; R. A. Makarov (Вестник анестезиологии и реаниматологии)
The pain relief in labor is one of the key components of the modern obstetrics. The multiple trials have been devoted to searching for the best way of pain relief, new methods are being developed and improved.The review tells about modern aspects and international experience when using the different variants of neuraxial methods of pain relief in labor, their impact on the satisfaction of the mother, maternal and neonatal outcomes.